In Situ Hydrolysis of Imine Derivatives on Au(111) for the Formation of Aromatic Mixed Self-Assembled Monolayers: Multitechnique Analysis of This Tunable Surface Modification - Luo, Ying; Bernien, Matthias; Hermanns, Christian Felix; Miguel, Jorge; Jaekel, Simon; Chang, Yin-Ming; Kuch, Wolfgang; Haag, Rainer; et al. (Langmuir, 2012)
This paper presents a novel method for preparing aromatic, mixed self-assembled monolayers (SAMs) with a dilute surface fraction coverage of protonated amine via in situ hydrolysis of C=N double bond on gold surface. Two imine compounds, (4'-(4-(trifluoromethyl)benzylideneamino) biphenyl-4-yl)methanethiol (CF3-C6H4-CH=N-C6H4- C6H4-CH2-SH, TFBABPMT) and (4'-(4-cyanobenzylideneamino)biphenyl-4-yl)methanethiol (CN-C6H4-CH=N-C6H4-C6H4-CH2-SH, CBABPMT), self-assembled on Au(111) to form highly ordered monolayers, which was demonstrated by infrared reflection absorption spectroscopy (IRRAS) and X-ray photoelectron spectroscopy (XPS). A nearly upright molecular orientation for CF3- and CN-terminated SAM was detected by near edge X-ray absorption fine structure (NEXAFS) measurements. Afterward, the acidic catalyzed hydrolysis was carried out in chloroform or an aqueous solution of acetic acid (pH = 3). Systematic studies of this hydrolysis process for CN-terminated SAM in acetic acid at 25 C were performed by NEXAFS measurements. It was found that about 30% of the imine double bonds gradually cleaved in the first 40 min. Subsequently, a larger hydrolysis rate was observed due to the freer penetration of acetic acid in the SAM and resultant more open molecular packing. Furthermore, the molecular orientation in mixed SAMs did not change during the whole hydrolysis process. This partially hydrolyzed surface contains a controlled amount of free amines/ammonium ions which can be used for further chemical modifications.